Holistic care in advanced pseudomyxoma peritonei: the clinical nurse specialist role in a rare malignancy of the abdomen and pelvis. (2nd September 2020) - Staunton, Oonagh
Abstract : This article explores the complexities of providing holistic nursing care to patients with pseudomyxoma peritonei (PMP), an uncommon cancer of the abdomen and pelvis. It focuses on patients diagnosed at an advanced stage. Patient outcomes can be optimised with robust specialist referral pathways, effective communication and increased professional awareness of rare diseases. The quality of care can be assured with service development and innovation at the point of delivery, backed up by ongoing training, support and best-practice guidelines. The clinical nurse specialist plays an especially vital role in advanced PMP. This involves co-ordination of multidisciplinary care and community support. It also includes patient advocacy, clinical consultancy and psychosocial support, as well as the personalisation of patient-centred care and education for the many and varied individual needs of patients and their families at a very emotive time. This is demonstrated in a national specialised service that was established In Ireland in 2013. It serves patients with rare peritoneal malignancies, who had previously had to travel to the UK for surgical management. The service has continued to develop in practice and innovation for this patient cohort.